2019
DOI: 10.3727/096504018x15202945197589
|View full text |Cite
|
Sign up to set email alerts
|

H19 Facilitates Tongue Squamous Cell Carcinoma Migration and Invasion via Sponging miR-let-7

Abstract: The long noncoding RNA (lncRNA) H19 has been described to participate in various tumors metastasis. Nevertheless, whether H19 promotes or impedestongue squamous cell carcinoma (TSCC) cells migration and invasion remains controversial. Here, we found that the expression of H19 was elevated in TSCC tissues compared with adjacent normal tissues. Moreover, we demonstrated that the expression of H19 was higher in metastasized tumors compared with un-metastasized tumors. Consistently, TSCC cells express higher level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 36 publications
1
42
0
Order By: Relevance
“…For HNSCC specifically, a study by Guan et al [39] demonstrated that overexpression of H19 is associated with tumor recurrence and poor prognosis by performing an experiment including 62 HNSCC patients (46 with LSCC and 14 with HSCC). A very recent study [40] also showed that the expression level of H19 was higher in patients with metastasized (vs non-metastasized) tongue squamous cell carcinoma, and was higher in tumor cells than normal squamous cells.…”
Section: Discussionmentioning
confidence: 87%
“…For HNSCC specifically, a study by Guan et al [39] demonstrated that overexpression of H19 is associated with tumor recurrence and poor prognosis by performing an experiment including 62 HNSCC patients (46 with LSCC and 14 with HSCC). A very recent study [40] also showed that the expression level of H19 was higher in patients with metastasized (vs non-metastasized) tongue squamous cell carcinoma, and was higher in tumor cells than normal squamous cells.…”
Section: Discussionmentioning
confidence: 87%
“…Intriguingly, let-7a suppression significantly rescues the weakened tumor cell motility induced by sh-H19. These findings demonstrate that the H19/let-7a crosstalk plays a critical role in TSCC migration and invasion ( 37 ). Meanwhile, H19 is validated to regulate EZH2 by miR-630 silencing, which is a repressor of EZH2 and interacts with H19 in a sequence-specific manner, to inhibit the expression level of E-cadherin and eventually accelerate the invasion and metastasis of NPC ( 58 ).…”
Section: Lncrna/microrna Interaction In Hnscc Metastasismentioning
confidence: 82%
“…Furthermore, the expression level of H19 in metastatic tumor is significantly higher than in non-metastatic tumor. Subsequently, H19 is demonstrated to function as ceRNA to sponge let-7a, resulting in HMGA2 enhancement, and finally, increasing the capacity of TSCC invasion and metastasis ( 37 ). H19 is also found to be overexpressed in nasopharyngeal carcinoma (NPC) and to promote NPC cell invasion capacity via E-cadherin silencing and miR-630/EZH2 regulation ( 58 ).…”
Section: Lncrnas Involved In Hnscc Invasion and Metastasismentioning
confidence: 99%
“…This H19/let‐7a/HMGA2 axis finally promotes the expression of HMGA2, a key factor involved in the epithelial–mesenchymal transition (EMT). In CAL27 cells, H19 significantly impairs migration ability and invasion capacity (Kou et al, ).…”
Section: The Endogenous Rna Networkmentioning
confidence: 99%